1997
DOI: 10.1111/j.1439-0507.1997.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic effect of Carica papaya latex sap and fluconazole on Candida albicans growth

Abstract: A mixture of Carica papaya latex (0.41 mg protein ml-1) and fluconazole (2 micrograms ml-1) showed a synergistic action on the inhibition of Candida albicans growth. Thus, with this mixture an equivalent inhibition rate was observed to that obtained when C. albicans was cultured in a medium supplemented with a two-fold concentration (4 micrograms ml-1) of fluconazole alone. This synergistic effect resulted in partial cell wall degradation as indicated by transmission electron microscopy observations. An increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Others are Salvadora persica (Al-Bagieh et al, 1994), Balanites aegyptiaca (Saeed et al, 1995), Ocimum suave . Clutia abyssinica , Zanha africana (Fabry et al, 1996), Carica papaya (Giordani et al, 1991(Giordani et al, , 1996(Giordani et al, , 1997, Ozoroa insignis (Abreu et al, 1999) and Combretum molle (Khan et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others are Salvadora persica (Al-Bagieh et al, 1994), Balanites aegyptiaca (Saeed et al, 1995), Ocimum suave . Clutia abyssinica , Zanha africana (Fabry et al, 1996), Carica papaya (Giordani et al, 1991(Giordani et al, , 1996(Giordani et al, , 1997, Ozoroa insignis (Abreu et al, 1999) and Combretum molle (Khan et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The fruit of the plant from Angola is used for eczema and psoriasis (Bossard, 1993). The extracts of fruits, roots, latex and leaves of the plant from different countries were active against a number of microorganisms, including Candida albicans and other species of Candida and other fungi (Emeruwa et al, 1982;Gundidza, 1986;Caceres et al, 1995;Giordani et al, 1991Giordani et al, , 1996Giordani et al, , 1997.…”
Section: Carica Papayamentioning
confidence: 99%
“…To find suitable drug for the management of fungal diseases is difficult because fungi, like human beings, are eukaryotes. Giordani, et al (1997) reported the antifungal activity of C. papaya latex sap against Candida albicans. Carica papaya latex sap inhibits the growth of Candida albicans when added to a culture during the exponential growth phase.…”
Section: Anthelmintic Propertiesmentioning
confidence: 99%
“…Okeniyi, et al (2007) reported that seeds of Papaya have both antimicrobial and antihelmintic activities. The latex of Papaya and fluconazole has synergistic action on the inhibition of the growth of Candida albicans (Giordani, et al, 1997, Roshan, et al, 2014. Carica papaya plants produce natural compounds in leaf bark and twig tissues that possess both highly anti-tumour and pesticidal properties (Jaiswal, et al, 2010.…”
Section: Medicinal Propertiesmentioning
confidence: 99%
“…Giordani's research showed the antifungal activity of papaya latex against Candida albicans with inhibitory effect of approximately 60%, and a synergistic action when mixing latex with fluconazole (Giordani et al, 1997, Giordani et al, 1996.…”
Section: Salmonella Typhi Staphylococcus Aureus Proteus Vulgaris Pmentioning
confidence: 99%